Cariostatic effect of fluoride-containing restorative materials associated with fluoride gels on root dentin - BORGES, Fernanda Tavares (J Appl Oral Sci, 2010)
Secondary caries is still the main cause of restoration replacement, especially on the root surface OBJECTIVE: This in vitro study evaluated the cariostatic effects of fluoride-containing restorative materials associated with fluoride gels, on root dentin. MATERIALS AND METHODS: A randomized complete block design was used to test the effects of the restorative systems, fluoride regimes and the interactions among them at different distances from restoration margins. Standardized cavities were prepared on 240 bovine root specimens and randomly assigned to 15 groups of treatments (n=16). Cavities were filled with the following restorative materials: Ketac-Fil (3M-ESPE); Vitremer (3M-ESPE); Dyract/Prime & Bond NT (Dentsply); Charisma/Gluma One Bond (Heraeus Kulzer) and the control, Z250/Single Bond (3M-ESPE). The specimens were subjected to a pH-cycling model designed to simulate highcaries activity. During the cycles, 1.23% acidulated phosphate fluoride, 2.0% neutral sodium fluoride or deionized/distilled water (control) was applied to the specimens for 4 min. The surface Knoop microhardness test was performed before (KHN(i)) and after (KHN(f)) the pH cycles at 100, 200 and 300 mm from the margins. Dentin microhardness loss was represented by the difference in initial and final values (KHN(i) - KHN(f)). Data were analyzed by Friedman's and Wilcoxon's tests, ANOVA and Tukey's test (α=5%). RESULTS: The interaction of restorative systems and topical treatments was not significant (p=0.102). Dentin microhardness loss was lowest closer to the restoration. Ketac-fil presented the highest cariostatic effect. Vitremer presented a moderate effect, while Dyract and Charisma did not differ from the control, Z250. The effects of neutral and acidulated fluoride gels were similar to each other and higher than the control. CONCLUSION: Conventional and resin-modified glass ionomer cements as well as neutral and acidulated fluoride gels inhibit the progression of artificial caries adjacent to restorations. The associated effect of fluoride-containing restorative materials and gels could not be demonstrated.